Strategi Pemerintah dalam mencegah paham Radikalisme Di Era Penggunaan Media social di kalangan remaja - Maksin, Mastina Tina (Journal of Humanity Studies, 2022)
Radicalism is an ideology or flow that wants social and political change or renewal by violent or drastic means, this is carried out by radical groups which justify various ways of carrying out their actions even though they take many victims, by justifying the teachings adhered to by these groups. As well as the radicalism network spreading various forms of propaganda to openly recruiting group members through social media or the internet, so that this becomes a problem where based on BPS data the population in Indonesia is dominated by productive groups, namely young people who are included in the category of Millennials and Generations "Z" so that this becomes a form of special concern because it can become a time bomb in the future if these teenagers are trapped and take part in the ideology of radicalism which ends in acts of terrorism. As for the method used in this research or writing, it uses a qualitative descriptive method with the hope that it can contain an in-depth and specific description or description of an article or a matter observed by the researcher. With the method used, it can be concluded that there are several strategies made by the government through the National Counterterrorism Agency (BNPT) and through the Ministry of Religion in counteracting radicalism in the era of social media use among adolescents.